The Urgency of Regulation of Electric Bikes in Gorontalo City in a Progressive Legal Perspective - Puluhulawa, Mohamad Rusdiyanto U.; Puluhulawa, Jufryanto; Swarianata, Vifi; Biya, Fitriana Nur (Universitas Negeri Gorontalo, 2022)
The use of electric bicycles is currently becoming a primadonna among the community. The combination of transportation and technology makes it a creative and revolutionary innovation. High public interest and also based on the thought of the movement to save the Earth from carbon emissions has increasingly popularized the use of electric bicycles. The purpose of this study was to determine and analyze the urgency of regulating electric bicycles in Gorontalo City in a progressive legal perspective. The research method used is statute approach and conceptual approach. Electric bicycles have begun to be traded in the Gorontalo Province. Of course, this indicates that Gorontalo Province has good market potential. Nationally, the rules for the use of electric bicycles have indeed been accommodated in the Minister of Transportation Regulation, but their embodiment in regional regulations is still needed considering that Gorontalo Province in general and Gorontalo City in particular certainly have special conditions. which must also be accommodated in a regulation because the facilities and infrastructure as well as local wisdom that live in the community are certainly not at the same level nationally. It is appropriate that the use of electric bicycles as a means of transportation is made a legal umbrella in the regions. Law through the lens of progressiveness must move faster than society itself considering that law is rigid while society is dynamic